DAMPAK BENCANA BANJIR DAN MITIGASI DI NAGARI PANGKALAN KECAMATAN PANGKALAN KOTO BARU - azhari ramadhan ramadhan (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to seek information and find out about (1) the impact of the Flood Disaster on the Community in Nagari Pangkalan, Pangkalan Koto Baru District. (2) flood disaster management efforts in Nagari Pangkalan Pangkalan Koto Baru District. The type of research used in this research is the type of research mix method is a combination of quantitative approaches and qualitative approaches. data collection techniques use questionnaires, documentation and interviews. The population in this study is Jorong Lakuak Gadang and Jorong Lubuak Nago with random sampling. Conclusion (1) in this study there are 4 Affected areas, namely the physical, social, environmental and economic sectors. (2) Government mitigation efforts by providing training on disaster mitigation and complementing disaster mitigation infrastructure and warning the public to remain vigilant